Evaluating the Development Experience in Open Science Tools: A Case Study of the dataWASHES API - Souza, Antônio; Viana, Davi; Santos, Rodrigo; Araújo, Allysson Allex (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2025: Anais do X Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2025.8006, 2025)
Open science has gained prominence in Software Engineering research, yet Developer Experience (DX) in open science tools remains an underexplored topic. Recognizing this relevance, this study investigates developers’ perceptions of DX when using dataWASHES, an open source API that facilitates access to WASHES proceedings data. A qualitative study was conducted with 13 participants performing scenario-based tasks using the API, followed by a questionnaire inspired by the SPACE framework. Results indicate a positive DX, with 84.6% of participants rating their experience at the highest level. While satisfaction and efficiency were strengths, minor usability issues suggest areas for improvement. Analyzing DX in tools like dataWASHES advances our understanding of the relationship between open science tools and DX, providing important lessons towards the engineering of open science solutions.